Necessary optimality conditions for nonsmooth robust optimization problems. (3rd July 2022) - Wei, Hong-Zhi; Chen, Chun-Rong; Li, Sheng-Jie
ABSTRACT: In this paper, we investigate robust necessary optimality for scalar uncertain optimization problems under the strictly robust counterpart, where the uncertainties are included in the objective and the constraints. Based on generalized differentiable assumptions, some robust necessary conditions via a separation scheme are derived. Besides, by means of strong separation functions, several characterizations of robust necessary optimality can be established. Finally, an example is given to show the effectiveness of the results derived in this paper.